Pembrolizumab and decitabine for refractory or relapsed acute myeloid leukemia. Issue 1 (11th January 2022) - Goswami, Meghali; Gui, Gege; Dillon, Laura W; Lindblad, Katherine E; Thompson, Julie; Valdez, Janet; Kim, Dong-Yun; Ghannam, Jack Y; Oetjen, Karolyn A; Destefano, Christin B; Smith, Dana M; Tekleab, Hanna; et al.
Abstract : Background: The powerful 'graft versus leukemia' effect thought partly responsible for the therapeutic effect of allogeneic hematopoietic cell transplantation in acute myeloid leukemia (AML) provides rationale for investigation of immune-based therapies in this high-risk blood cancer. There is considerable preclinical evidence for potential synergy between PD-1 immune checkpoint blockade and the hypomethylating agents already commonly used for this disease. Methods: We report here the results of 17 H-0026 (PD-AML, NCT02996474 ), an investigator sponsored, single-institution, single-arm open-label 10-subject pilot study to test the feasibility of the first-in-human combination of pembrolizumab and decitabine in adult patients with refractory or relapsed AML (R-AML). Results: In this cohort of previously treated patients, this novel combination of anti-PD-1 and hypomethylating therapy was feasible and associated with a best response of stable disease or better in 6 of 10 patients. Considerable immunological changes were identified using T cell receptor β sequencing as well as single-cell immunophenotypic and RNA expression analyses on sorted CD3+ T cells in patients who developed immune-related adverse events (irAEs) during treatment. Clonal T cell expansions occurred at irAE onset; single-cell sequencing demonstrated that these expanded clones were predominately CD8+ effector memory T cells with high cell surface PD-1 expression and transcriptional profiles indicative of activation and cytotoxicity. In contrast, no such distinctive immune changes were detectable in those experiencing a measurable antileukemic response during treatment. Conclusion: Addition of pembrolizumab to 10-day decitabine therapy was clinically feasible in patients with R-AML, with immunological changes from PD-1 blockade observed in patients experiencing irAEs.